Social Network Analysis as a research method in political science. An attempt to use it in coalition research - Żukiewicz, Przemysław; Zieliński, Mateusz; Domagała, Katarzyna (Przegląd Politologiczny, 2018)
The main aim of the article is to argue the need for better focus of researchers conducting their research in the field of political science on some digital analytical tools used in social network analyses. Additional objectives are to outline the historical context of SNA’s development in this discipline, as well as to present possible fields of exploration and using of this method, both in basic and in applied research. Particular attention was paid to the potential of SNA in the study of the processes of cabinet coalitions formation, as well as to the important limitations of this method. The article was constructed as a methodological essay. We inevitably accept - because of its focus on network analyses a structural perspective on social reality. We verify the hypothesis that the greatest potential of SNA could be currently to create a visualization of social relations based on large data sets, but at the same time the most important barrier to the development of the method are limitations in the access to these data, which could be used as a basic analytical material for visualization of the network and generalization of the statistical conclusions. Presenting some political science research in Poland and around the world, in which SNA tools are used, we used the historical as well as the case study method.